Pengaruh Pemberian Jus Asam Jawa Secara Oral terhadap Profil Farmakokinetika Asetosal pada Kelinci Jantan New Zealand White - PENI GIYAN UTAMI; - SOETARNO; ENDANG SRI REJEKI (Jurnal Farmasi Indonesia, 2012)
Acetosal is the oldest of pain medication which till now the most widely used worldwide and very effective to relieve pain with mild to moderate intensity, but so far the public lack an understanding of the role of food and beverages included when taking the drug. Tamarind juice is a beverage that contains acid, which acetosal also has acidic properties. If acetosal consumed together with the tamarind juice, it will cause gastric pH increases so the absorption of acetosal is increasing. The experiment was aimed to know the influence of tamarind juice given orally on acetosal pharmacokinetic profile in New Zealand White male rabbits. This experiment was divided into two groups i.e. control group and treatment group. The control group was given acetosal of 70 mg/1.5kg BW of rabbit, and the treatment group was given acetosal of 70 mg/1.5kg BW of rabbit and tamarind juice of 17.5 ml/1.5kgBW. Blood was drawn through marginal vena with sampling time at minute 5, 10, 15, 20, 30, 40, 50, 60, 120, 180, 240, 300 and 360. Determination of total salisylic acid level in blood was done by UV-Vis spectrophotometer according to modified different method. The result of the experiment showed that tamarind juice affected the pharmacokinetic profile of acetosal indicated by value increased of Ka, ClT, Vc, Vdss, and t½ β and value decreased of t max, K21, K, K12, AUC, α, and β